Affective Valence of Words Differentially Affects Visual and Auditory Word Recognition - Gao, Chuanji (J Exp Psychol Gen, 2022)
Recognizing written or spoken words involves a sequence of processing stages, transforming sensory features into lexical-semantic representations. While the later processing stages are common across modalities, the initial stages are modality-specific. In the visual modality, previous studies have shown that words with positive valence are recognized faster than neutral words. Here, we examined whether the effects of valence on word recognition are specific to the visual modality or are common across visual and auditory modalities. To address this question, we analyzed multiple large databases of visual and auditory lexical decision tasks, relating the valence of words to lexical decision times while controlling for a large number of variables, including arousal and frequency. We found that valence differentially influenced visual and auditory word recognition. Valence had an asymmetric effect on visual lexical decision times, primarily speeding up recognition of positive words. By contrast, valence had a symmetric effect on auditory lexical decision times, with both negative and positive words speeding up word recognition relative to neutral words. The modality-specificity of valence effects were consistent across databases and were observed when the same set of words were compared across modalities. We interpret these findings as indicating that valence influences word recognition partly at the sensory-perceptual stage. We relate these effects to the effects of positive (reward) and negative (punishment) reinforcers on perception.